La portée réparatrice et réconciliatrice de la Commission de vérité et réconciliation du Canada - Jaccoud, Mylène (Recherches amérindiennes au Québec, 2016)
Cet article examine les potentialités réparatrices et réconciliatrices de la Commission de vérité et réconciliation (CVR) qui a été mise en place au Canada de 2008 à 2015 en réponse aux traumatismes vécus par les autochtones dans les pensionnats. L’auteure conclut que ces potentialités sont relativement limitées. Les principales limites tiennent à l’absence d’un espace de dialogue entre les victimes et les responsables, à une centration sur les narratifs traumatiques des victimes mais aussi à une conception dépolitisée du principe de la réconciliation. La CVR du Canada n’a pas inscrit la décolonisation comme vecteur de réconciliation mais a préféré s’engager dans la voie d’une pacification des relations entre les peuples. Or, l’auteure soutient que la réconciliation entre les peuples autochtones et l’État nécessite de dépasser les gestes de guérison et de réparation matérielle ou symbolique. La décolonisation des institutions, la redistribution des territoires et une réforme constitutionnelle en profondeur restent les seules avenues possibles pour parvenir à réconcilier avec ses oppresseurs un peuple victime d’un génocide culturel.
Keywords: 2000 à aujourd'hui; 2010-2019; amériques; approches et analyses; canada; capitalisme; commission de vérité et réconciliation; cours; criminologie; discipline; droits des personnes autochtones; féminisme décolonial; histoire et politique; justice réparatrice; justice sociale; peuples autochtones; pol4102; premier cycle; périodes historiques; racisme; réconciliation; régions géographiques; sciences humaines; système colonial; systèmes d'oppressions; thématiques; violences

Prison sexual abuse: Race, gender, and the rule of law - Buchanan, Kim (Columbia University, 2010)
In this dissertation, I argue that the exemption of prisons from the rule of law fosters abusive institutional practices that reveal the race and gender dynamics of sexual abuse in prison and in the outside world. The first article, Beyond Modesty: Privacy in Prison and the Risk of Sexual Abuse, shows that Fourth Amendment privacy offers little protection against the cross-gender searches and surveillance that expose women prisoners to sexual abuse by male guards. It proposes a reinterpretation of Fourth Amendment privacy that would recognize a constitutional right to be free from the fear, risk and reality of prison sexual abuse. The second article, Impunity: Sexual Abuse in Women's Prisons, shows that an edifice of constitutional, statutory and common-law rules confers near-complete institutional immunity against nearly all prisoner claims of custodial sexual abuse. These immunity rules parallel those of historical status regimes which excluded low-status litigants from courts on the basis of race and gender, such as civil death, slavery, segregation and the common law of marriage and rape–with similar results: low-status women of color are exposed to systematic and institutionalized sexual abuse, and are prevented from seeking protection or redress from the courts. The third article, Our Prisons, Ourselves: Race, Gender and the Rule of Law, develops these insights in men's prisons. In the absence of enforceable external rules, staff and administrators often adopt a gendered practice of institutional governance that requires prisoners to prove their manhood by fighting, and penalizes unmanly men by allowing others to rape them. These unlawful gendered practices are obscured by a false but powerful racialized narrative: most people inside and outside prison believe, inaccurately, that prison rape is mainly black-on-white. By casting sexual violence as a "complex and intractable" race relations problem for which administrators are not to blame, the racial narrative bolsters the rationale for exempting prison administration from the rule of law. Thus the perception (and reality) of unchecked prison violence supplies a reason for courts not to interfere with the unlawful institutional policies that foster it.
https://clio.columbia.edu/catalog/8481765
Keywords: approches et analyses; criminologie; discipline; droit; genre; intersectionnalité; mémoires/thèses; racisme; ressource en ligne; science politique et droit; sciences humaines; sexisme; systèmes d'oppressions; thématiques; violences; violences sexuelles